(untitled) (Journal of Life and Earth Science, 2014)
An experiment was conducted to determine the heavy metal pollution status of selected six ponds in Rajshahi City Corporation for a period of 7 months from June, 2008 to December, 2008. Among heavy metals the mean values of Cu, Mn, Zn, Fe and Pb varied from 0.05±0.02 (Pond-5) to 1.79±0.88 mg/l (Pond-4), 21.30±2.64 (Pond-6) to 76.57±30.90 mg/l (Pond-1), 0.08±0.02 (Pond-6) to 1.25±0.79 mg/l (Pond-4), 0.75±0.10 (Pond-3) to 1.87±0.53 mg/l (Pond-5) and 0.14±0.12 (Pond-6) to 4.92±1.66 mg/l (Pond-4) respectively. This study indicated that the Pond-2 covered by garbage, polythene and other wastes, Pond-3 and Pond-4 received industrial wastes were moderately polluted whereas the Pond-1 received City corporation wastes was less polluted. DOI: http://dx.doi.org/10.3329/jles.v7i0.20131 J. Life Earth Sci., Vol. 7: 115-117, 2012